Adaptation of Prunus serotina to rehabilitate degraded semi-arid soils - Balderas-Zamorano, Gerardo Emilio; Buendía-Espinoza, Julio César; Martínez-Ochoa, Elisa del Carmen; García-Núñez, Rosa María; Zamora-Elizalde, Mayra Clementina (Revista Mexicana de Ciencias Agrícolas, 2026)
The rehabilitation of degraded soils in semi-arid areas requires woody species with high water-stress tolerance and the potential to provide ecosystem services. Prunus serotina has been characterized as tolerant to water stress and having low soil requirements, in addition to presenting rapid growth; however, there is little recent evidence on its initial performance in semi-arid conditions in Mexico. The objective was to evaluate the early adaptation of P. serotina in the field and to estimate its regional environmental suitability. The study was conducted from 2021 to 2022 in Nopaltepec (Tula River Basin, State of Mexico, Mexico). A plantation trial was established with survival and growth monitoring; survival was analyzed using the Kaplan-Meier estimator and factors associated with mortality risk were analyzed using a Cox proportional hazards model. Environmental suitability was modeled with MaxEnt using bioclimatic and topographic variables; performance was verified using AUC and TSS and a suitability map was generated. Survival at 12 months was  and final diameter was associated with a lower risk of mortality , suggesting that a greater allocation to structural reserves improves stress tolerance. In the SDMs, annual precipitation, thermal seasonality and altitude contributed significantly, delimiting areas with high suitability in and around the basin. It was concluded that P. serotina is a viable option for restoration initiatives in semi-arid environments, recommending selection based on initial size, protection against mechanical damage and drought, and establishment in favorable climatic windows.
Keywords: Prunus serotina; habitat suitability; mortality risk; survival